Figures S1-S4, Tables S1-S2 from Fear the reaper: ungulate carcasses may generate an ephemeral landscape of fear for rodents - S. C. Frank; R. Blaalid; M. Mayer; A. Zedrosser; S. M. J. G. Steyaert (2020)
Fig S1: Changes in percent cover for covariates , Fig S2: Semivariograms, Fig S3: Probability of changes to rodent presence against changes in bird abundance 2017-2018, Fig S4: Camera trap image with raven, Table S1: Model selection results, Table S2: Model diagnostics